The Washington, DC Media Corps in the 21st Century - Hellmüller, L. author. aut Link
XII, 192 p. 17 illus.
Keywords: The book provides a fresh perspective on the shifting media landscape within Washington DC, re-evaluating journalist-source relationships, the power dynamic within the media corps, and the ways in which technology have changed the description of DC political news - detailing the ways in which media relationships are changing within Washington DC.